Glucose-6-Phosphate Dehydrogenase Deficiency in the Dr. Cipto Mangunkusumo General Hospital - Rulina Suradi; H.E. Monitja; Bulan G. Munthe; Suparno Suparno (Indonesian Pediatric Society, 1979)
The incidence of G-6-P-D deficiency in Indonesia is not yet known. So far only Inyo Luan Eng (1964) reported the incidence in some parts of Indonesia. Other data are only from case reports. This study which consisted of 3200 babies – born in the Dr. Cipto Mangunkusumo General Hospital from September 1975 through October 1976 proved that the incidence is high enough that is 2.66% (85 out of 3200). The hemoglobin content of G-6-P-D deficient babies showed an average of 14.4 g%. This gives us an idea that there is slight anemia in these babies. The incidence of jaundice was 35 out of 85 (41%). Factors inducing jaundice were infection, hypoxia and sub-aponeurotic bleeding. Of 60 which could be examined quantitatively only 2 showed a G-6-P-D activity level of more than 120 mu/10^9 RBC, so that the screening method could be used for early detection of G-6-P-D deficiency.